Connections Across the Colonial Divide: The Colenso Family and the Zulu Royal Family in Natal and Zululand - Gwilym Colenso (Genealogy, 2025)
In late nineteenth-century Natal, members of the family of the missionary Bishop John William Colenso established relations with members of the Zulu royal family that were recognised as ties of kinship, mutually acknowledged by the reciprocal use of kinship terms between the two families. The Colenso family played a part in the struggle to defend Zulu sovereignty in the face of a colonial government intent on undermining the Zulu nation by diminishing the authority of the Zulu King. The visit by the Zulu king, Cetshwayo, to Queen Victoria in 1882 was seen by subsequent generations of Zulu as evidence of a connection between the British and Zulu royal families. While in exile on the island of St Helena, through adopting western dress and lifestyle, Cetshwayo’s son, Dinuzulu, sought to model his family on the British royal family. Bishop Colenso’s daughter, Harriette, played a role in facilitating this image, appearing as if a matriarch of Dinuzulu’s family in photographs which were perhaps intended to compare the two royal families, while also conveying a strong message that succession to the throne was secured by heredity, a message conveyed in representations of the British royal family from the sixteenth century to the present.